PENERAPAN STRATEGI PEMBELAJARAN AKTIF SEPAK BOLA VERBAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI IPA MAN KAMPAR - Dian Ekanatalia; Mitri Irianti; Zuhdi Ma’aruf (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: This study aims to describe and know differences in student learning outcomes by applying active strategies of verbal soccer. The type of research used is Pre-ekspremental with intact-group comparison design. The population of this study were students of class XI IPA MAN Kampar amounted of 70 students consisting 2 classes, each control class and experiment class. The data in this study is the score of student learning outcomes obtained after active learning of verbal soccer and analyzed descriptively and inferentially. The results showed that there are differences in student learning outcomes that apply the active learning strategy of verbal soccer with conventional class. The average absorptive capacity of the class that implements the active learning strategy of verbal soccer is 80.79%, while the absorption rate of the conventional class is 72.79%. Thus it can be concluded that the implementation of the active strategy of verbal soccer can improve student learning outcomes class XI IPA MAN Kampar.Key Words: learning active strategy verbal soccer , learning result